Epigenetic Alterations in Renal Cell Cancer With TKIs Resistance: From Mechanisms to Clinical Applications - Li, Qinhan; Zhang, Zhenan; Fan, Yu; Zhang, Qian (Frontiers in Genetics, 2021)
The appearance of tyrosine kinase inhibitors (TKIs) has been a major breakthrough in renal cell carcinoma (RCC) therapy. Unfortunately, a portion of patients with TKIs resistance experiences disease progression after TKIs therapy. Epigenetic alterations play an important role in development of TKIs resistance. Current evidence suggests that epigenetic alterations occur frequently in RCC patients with poor response to TKIs therapy, and modulation of them could enhance the cytotoxic effect of antitumor therapy. In this review, we summarize the currently known epigenetic alterations relating to TKIs resistance in RCC, focusing on DNA methylation, ncRNAs, histone modifications, and their interactions with TKIs treatment. In addition, we discuss application of epigenetic alteration analyses in the clinical setting to predict prognosis of patients with TKIs treatment, and the potential use of epigenetics-based therapies to surmount TKIs resistance.